2015
DOI: 10.1155/2015/458470
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diet and Exercise on the Peripheral Immune System in Young Balb/c Mice

Abstract: Although diet and exercise clearly have an influence on immune function, studies are scarce on the effect caused by exercise and the consumption of a carbohydrate-rich or fat-rich diet on the peripheral immune system. The aim of the present study was to evaluate the effect of exercise and the two aforementioned unbalanced diets on young Balb/c mice, especially in relation to BMI, the level of glucose, and the percentage of lymphocyte subpopulations in peripheral blood. The changes found were then related to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 90 publications
1
5
0
Order By: Relevance
“…A dietary intervention RCT of 91 women who were obese demonstrated that weight loss was associated with a decrease in mitogen-stimulated lymphocyte proliferation, a component of innate and adaptive immunity, but not NK cell cytotoxicity 197 . Similar effects were noted in preclinical studies, as dietary interventions altered the peripheral immune system, as measured by the percentage of lymphocyte subpopulations in peripheral blood 198 .…”
Section: Biological Mechanismssupporting
confidence: 68%
“…A dietary intervention RCT of 91 women who were obese demonstrated that weight loss was associated with a decrease in mitogen-stimulated lymphocyte proliferation, a component of innate and adaptive immunity, but not NK cell cytotoxicity 197 . Similar effects were noted in preclinical studies, as dietary interventions altered the peripheral immune system, as measured by the percentage of lymphocyte subpopulations in peripheral blood 198 .…”
Section: Biological Mechanismssupporting
confidence: 68%
“…Accordingly, db/db and ob/ob presented a reduced number of peripheral blood and bone marrow B lymphocytes, which was recovered after leptin treatment ( Bennett et al, 1996 ; Claycombe et al, 2008 ). Conversely, db/db mice presented an increased absolute number of B cells in the peritoneal cavity ( Jennbacken et al, 2013 ), and the increase of leptin was correlated with a decrease in B cells of mice with unbalanced diets (carbohydrate-rich and fat-rich) ( Martínez-Carrillo et al, 2015 ). Thus, further investigation is needed to better clarify the role of leptin in lymphopoiesis.…”
Section: Leptin and Adaptive Immunity ( Figure mentioning
confidence: 99%
“…Also, because they are not obese strains such as db/db and ob/ob mice. This allows us to evaluate the effect of diets and different nutrients in a healthy animal model [45,46,47,48]. The objective of using this strain was to work with healthy rodent models, to know the effect of sweeteners on healthy subjects before the disease is established.…”
Section: Methodsmentioning
confidence: 99%